Implementation of Search Engine Optimization on Lampung Tourism Websites Using The On-Page Method - Alhafizh, Muhammad Aqil; Ahmad, Imam (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The tourism sector has become a vital driver of economic growth and social development in various regions, including Lampung. Between 2016 and 2022, Lampung experienced significant fluctuations in tourist numbers, particularly affected by the COVID-19 pandemic. Despite the challenges, the resurgence of tourism in 2022 underscores the importance of effective promotion and visibility, largely facilitated by websites. Search Engine Optimization (SEO) plays a crucial role in enhancing website visibility on Search Engines like Google, Bing, and Yahoo. This research aims to analyze the application of SEO techniques on the Lampung Tourism website. It investigates how on-page SEO methods, such as keyword optimization, meta tags, and website structure, influence website rankings on Google's Search Engine Results Pages (SERP). Additionally, the study examines the impact of appropriate SEO strategies using SEO testing tools. Using a quantitative methodology, specifically an experimental approach, this study implements specific SEO techniques on the Lampung tourism website over a two-month period. Key steps include problem identification, literature review, keyword analysis, on-page SEO implementation, post-testing, and conclusion drawing. The research employs tools like Google Keyword Planner, Yoast SEO, and SEOptimer for data collection, analysis, and optimization. The study demonstrates that the application of on-page SEO techniques effectively improves the ranking of the Lampung Tourism website, contributing to its visibility and competitiveness online.